Error management theory and the adaptive significance of transgenerational maternal‐stress effects on offspring phenotype. Issue 13 (2nd June 2018) - Sheriff, Michael J.; Dantzer, Ben; Love, Oliver P.; Orrock, John L.
Abstract: It is well established that circulating maternal stress hormones (glucocorticoids, GCs) can alter offspring phenotype. There is also a growing body of empirical work, within ecology and evolution, indicating that maternal GCs link the environment experienced by the mother during gestation with changes in offspring phenotype. These changes are considered to be adaptive if the maternal environment matches the offspring's environment and maladaptive if it does not. While these ideas are conceptually sound, we lack a testable framework that can be used to investigate the fitness costs and benefits of altered offspring phenotypes across relevant future environments. We present error management theory as the foundation for a framework that can be used to assess the adaptive potential of maternal stress hormones on offspring phenotype across relevant postnatal scenarios. To encourage rigorous testing of our framework, we provide field‐testable hypotheses regarding the potential adaptive role of maternal stress across a diverse array of taxa and life histories, as well as suggestions regarding how our framework might provide insight into past, present, and future research. This perspective provides an informed lens through which to design and interpret experiments on the effects of maternal stress, provides a framework for predicting and testing variation in maternal stress across and within taxa, and also highlights how rapid environmental change that induces maternal stress may lead to evolutionary traps. Abstract : This article provides a quantitative framework as a means of generating field‐testable hypotheses regarding the adaptive potential of maternal stress under different scenario combinations. By providing a mechanistic basis for examining the adaptive potential of maternal stress effects, our overall aim is not only to provide a means for explaining patterns and testing new hypotheses, but to catalyze the study of maternal stress effects under this framework across a diversity of species, life histories, and environments.